Roger Williams and the creation of the American soul : church, state, and the birth of liberty - Barry, John M., 1947- (New York : Viking, 2012)
An acclaimed historian and "New York Times"-bestselling author offers a revelatory look at how Roger Williams shaped the nature of religion, political power, and individual rights in America.
The law -- The covenant -- The new world -- The wilderness -- The mission -- Soul liberty -- The test.
Includes bibliographical references (p. 427-438) and index.
Keywords: Williams, Roger, -- 1604?-1683.